2022
DOI: 10.1186/s12911-022-01937-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymphedema occurrence in patients with breast cancer using the optimized combination of ensemble learning algorithm and feature selection

Abstract: Background Breast cancer-related lymphedema is one of the most important complications that adversely affect patients' quality of life. Lymphedema can be managed if its risk factors are known and can be modified. This study aimed to select an appropriate model to predict the risk of lymphedema and determine the factors affecting lymphedema. Method This study was conducted on data of 970 breast cancer patients with lymphedema referred to a lymphede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Isik et al reported in 2022, in a retrospective study of the BC database from 2013 to 2017, that patients with removal of more than 5 LNs were more likely to develop lymphedema (25). A 2022 study by Yaghoobi Notash et al, aiming to determine factors influencing lymphedema which was done on 970 patients with BC, the percentage of influencing variables was reported as follows: The number of LNs/the number of LNs isolated ratio (68%), the feeling of heaviness (67%), number of LNs isolated (64%), receiving radiotherapy (63%), surgery type (62%), number of involved LNs (61%), BMI (61%) (31). So both of these studies showed a significant association between the number of isolated LN-negatives and Lymphedema in patients same our study.…”
Section: Discussionmentioning
confidence: 99%
“…Isik et al reported in 2022, in a retrospective study of the BC database from 2013 to 2017, that patients with removal of more than 5 LNs were more likely to develop lymphedema (25). A 2022 study by Yaghoobi Notash et al, aiming to determine factors influencing lymphedema which was done on 970 patients with BC, the percentage of influencing variables was reported as follows: The number of LNs/the number of LNs isolated ratio (68%), the feeling of heaviness (67%), number of LNs isolated (64%), receiving radiotherapy (63%), surgery type (62%), number of involved LNs (61%), BMI (61%) (31). So both of these studies showed a significant association between the number of isolated LN-negatives and Lymphedema in patients same our study.…”
Section: Discussionmentioning
confidence: 99%
“…Notash et al. ( 37 ) used six classification algorithms including C5.0’s decision tree, KNN, SVM, LDA, Bayesian, and MLP to construct the BCRL prediction model, of which the SVM algorithm showed the highest sensitivity and was found to be the best model for predicting lymphedema, based on the accuracy obtained, the algorithm correctly detected the presence or absence of lymphedema in newly diagnosed patients in 88% of cases, which was slightly higher than the AUC of the LR in this study (0.87).Wei et al. ( 38 ) derived and evaluated six machine learning models, and the results showed that the LR model performed the best in the early detection of lymphedema with the best performance, AUC = 0.889 (0.840–0.938), sensitivity = 0.771, specificity = 0.883, accuracy = 0.825, and Brier score = 0.141, which is slightly lower than the sensitivity of LR (0.79) in this study.…”
Section: Discussionmentioning
confidence: 99%